The Skill of End-of-Life Communication for Clinicians : Getting to the Root of the Ethical Dilemma - Benton, Kathleen (Springer International Publishing : Imprint: Springer, 2017)
With a focus on end-of-life discussion in aging and chronically ill populations, this book offers insight into the skill of communicating in complex and emotionally charged discussions. This text is written for all clinicians and professionals in the fields of healthcare and public health who are faced with questions of ethical deliberation when a patient's illness turns from chronic to terminal. This skill is required to manage care well in an age of advanced technology, and numerous autonomous choices. With a palliative care and ethics focus, the manuscript provides case studies illustrating issues which occur in the acuity and chronicity of end of life. Clear tools for clinicians, such as scripting and "the advance care planning video library" are included. The book focuses on the unique concept of outpatient ethics, including readmission prevention and shortened length of stay through good communication for clinicians who will be required to conduct this discussion with patients. The ethical undertone in this text provides a perfect opening for application in healthcare ethics classes, both in fields of public health and healthcare. Medical scholars and physicians, nurse practitioners and physician's assistants, as well as social workers, both in practice and training, will benefit from this text.
Keywords: Medicine.; Bioethics.; Medical ethics.; elektronické knihy; electronic books